Simultaneous detection of three amphenicol antibiotics in shrimp and surface water samples by LC–MS/MS using two-antibodies-immobilized immunoaffinity clean-up technique. Issue 1 (1st January 2021) - Guo, Enhui; Zhao, Linchuan; Wu, Kang; Huang, Wen; Zhao, Kang; Li, Jianguo; Deng, Anping
ABSTRACT: Amphenicol antibiotics including chloramphenicol (CAP), florfenicol (FF) and thiamphenicol (TAP) have been widely used in aquaculture and veterinary to treat various infections. Because of their high toxicity, it is important to detect these amphenicol antibiotics simultaneously. Using the monoclonal antibody against CAP (mAbCAP ) binding CAP only and the mAbFF recognizing both FF and TAP, the two antibodies were covalently coupled to CNBr-activated Sepharose-4B for the simultaneous extraction of CAP, FF and TAP from samples. The bound CAP, FF and TAP were eluted from the Sepharose-4B and measured by LC–MS/MS. The extraction conditions of the two-antibodies-immobilized immunoaffinity clean-up (IAC) for CAP, FF and TAP were optimized and the maximum capacity was investigated. The extraction efficiency of IAC for CAP, FF and TAP was 1.1–2.1 times higher than that of SPE. The LC–MS/MS coupled with IAC was a powerful analytical method for the detection of CAP, FF and TAP simultaneously.